Reimagining Ecologies of Music and Sound through Soundscape Stories - Clarke, Emily (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
This article reimagines teaching and learning through soundscape storytelling and soundwalking as inquiry-based, place-responsive pedagogies. Emphasizing listening, sensory engagement, and relational learning, soundwalking connects participants to the cultural, ecological, and historical dimensions of their environments. Drawing on a series of participatory soundwalks in Vancouver, British Columbia, the study explores how walking, listening, and storytelling can expand approaches to music-making, illuminating the interconnectedness of sound, place, and identity. The work highlights themes of Indigenous knowledge, environmental sustainability, and the sonic legacies of place, offering a framework for integrating ecological and community-based sound practices into arts and music education. Engaging in these reflective and creative practices, the article calls for a more inclusive and responsive vision of learning, one that nurtures curiosity, ecological awareness, and critical connection in an increasingly interdependent world.